Systematic Literature Review: An overview of Digital Agriculture for Food Sustainability - Isiaka Kolawole Mustapha; Olalekan Busra Sakariyau; Umaru Mustapha Zubairu; Helen Andow Afang (LPPM of NAROTAMA UNIVERSITY, 2022)
Digital agriculture has been noted to have far reaching prospects in the transformation of agribusiness. Digital technologies are been applied to improve food production, processing, security and packaging. As most of the least developed and developing economies are strategizing to reduce poverty and hunger, digital agriculture presents opportunities to reverse the trends. Thus, this paper presents a systematic literature review with aim to collect all related research and identify gaps in digital agriculture, as well as to understand the benefits of digital technology in agriculture in other to chart new proposition for future studies. A systematic literature review was carried, and we have extracted 67 journals published within the last two decades (2002 -2022). Findings suggests that digital agriculture is important drivers of food sustainability, with improve production yield and increase household income. Also, 42% of the studies on digital agriculture are dominated by precision agriculture model. This SLR recognizes knowledge gaps in relation to the context, theory and content for future research.